Forgotten heroes, commemorations and tensions in the configurations of the past. Salta (Argentina), 1930s (Quinto Sol, 2022)
This article traces the tensions around the relationship between commemorations, monumentalization and history during the process of disciplinary institutionalization process in Salta (Argentina) at the first half of the twentieth century. The commemorative projects undertaken by the Junta de Estudios Históricos are analyzed, focusing on the historiographical and political basis of these interventions, the actors involved in a historiographic space in formation and the program of historiographic review proposed by the institution. In the context of the economic, political and social tensions at the interwar period and the need for an increasingly exhaustive control over sectors outside the ruling elites, social pressure and alternative memory projects are important in the ways in which the intellectual elites think about their provincial past, to look at projects written from the capital of the country, but also sensitive to the conflicts and tensions of the production space itself.
Keywords: Junta de Estudios Históricos de Salta; commemorations; patriotic liturgy